Pengaruh laju sedimentasi terhadap tutupan terumbu karang di perairan Kota Daruba, Kabupaten Pulau Morotai - Kismanto Koroy; Djainudin Alwi; Novaldo Geri Paraisu (Depik, 2020)
The coral reef is one of the invertebrate animals that inhabit the marine ecosystem with various aquatic biota. Physical environmental factors including sedimentation, strongly influence coral growth. This study aimed to analyze the percentage of coral cover and the sediment rates in the reclamation area of Daruba City, Morotai Island Regency. This research was carried out in November 2019 using the LIT method to calculate the percentage of coral cover and sediment trap to retrieve sedimentation data. The sediment trap was placed in the bottom waters for 14 days. Stratified filtering was used to separate the sediment, and analytical scales were used to measure dry sediment weight in grams. Sediment sample testing was conducted in the laboratory of the Faculty of Fisheries and Marine Sciences, Khairun University, Ternate. Measurement data were analyzed to calculate the percentage of coral cover and sediment rate analysis. The analysis showed that the percentage of live coral cover was in the range of 10.8 - 20.52%, this value indicates the condition of coral reefs in the waters of the village of Daruba and the waters of the reclaimed development area of the city of Daruba were in the poor category. Sedimentation rate in the reclamation area of the city of Daruba were 307,34 - 492,27 (g /cm2 /day).Keywords:Cover the reef,The rate of sediment,MorotaiABSTRAKTerumbu karang merupakan salah satu hewan avertebrata yang mendiami ekosistem dengan berbagai biota perairan. Pertumbuhan karang sangat dipengaruhi oleh faktor fisik lingkungan, salah satunya adalah sedimen. Tujuan penelitian ini yaitu menganalisis persentase tutupan karang dan menganalisis laju sedimen di area reklamasi kota Daruba Kabupaten Pulau Morotai. Penelitian ini dilakukan pada bulan November 2019 dengan menggunakan metode (LIT) untuk menghitung persentase tutupan karang dan pengambilan data sedimen menggunakan alat sediment trap yang ditempatkan di dasar perairan selama 14 hari. Selanjutnya dilakukan penyaringan bertingkat dan pengukuran berat kering sedimen dalam satuan gram dengan timbangan analitik. Pengujian sampel sedimen dilakukan di laboratorium Fakultas Perikanan dan Ilmu Kelautan Universitas Khairun Ternate. Data pengukuran dianalisis untuk menghitung persentase tutupan karang, dan analisis laju sedimen. Hasil analisis menunjukan persentase tutupan karang hidup berada pada kisaran 10,8 - 20,52%, nilai tersebut menunjukan kondisi terumbu karang di perairan desa Daruba dan area perairan pembangunan reklamasi kota Daruba termasuk dalam kategori buruk. Laju sedimentasi di perairan area reklamasi kota Daruba sebesar 307,34 - 492,27 (g/cm2/hari).Kata kunci:Tutupan karang, Laju sedimen,Morotai